2018
DOI: 10.1186/s13567-018-0597-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Salmonella Typhimurium adhesion, invasion, and intracellular survival via treatment with methyl gallate alone and in combination with marbofloxacin

Abstract: Salmonella enterica serovar Typhimurium infects intestinal epithelia and macrophages, which is prevented by inhibiting adhesion and cell invasion. This study aimed to investigate the role of methyl gallate (MG) in adhesion, invasion, and intracellular survival of Salmonella Typhimurium in Caco-2 and RAW 264.7 cells via a gentamicin protection assay, confocal microscopy, and quantitative reverse-transcription polymerase chain reaction. MG (30 µg/mL) inhibited adhesion and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Gut epithelial invasion and macrophage intracellular survival of Salmonella were performed in Caco-2 and RAW264.7, respectively, using a gentamicin protection assay as described previously with some modifications. 36 Briefly, overnight cultures of Salmonella were subcultured in LB with 0.3 M NaCl, and incubated at 200 rpm, 37°C for 3 hr. The bacterial cultures were washed using 1× PBS, and added into the cell lines at MOI = 20.…”
Section: Gut Epithelial Invasion and Macrophage Intracellular Survimentioning
confidence: 99%
“…Gut epithelial invasion and macrophage intracellular survival of Salmonella were performed in Caco-2 and RAW264.7, respectively, using a gentamicin protection assay as described previously with some modifications. 36 Briefly, overnight cultures of Salmonella were subcultured in LB with 0.3 M NaCl, and incubated at 200 rpm, 37°C for 3 hr. The bacterial cultures were washed using 1× PBS, and added into the cell lines at MOI = 20.…”
Section: Gut Epithelial Invasion and Macrophage Intracellular Survimentioning
confidence: 99%
“…It was demonstrated that the biofilms of Streptococcus mutans could be efficiently inhibited by the treatment of the phenolic compound, gallic acid (GA) [ 13 ]. A GA derivative, methyl gallate, was described in our recent reports for its inhibitory effects on the adhesion, invasion, and intracellular survival of Salmonella enterica serovar typhimurium , and for its interfering effects on Pseudomonas aeruginosa quorum-sensing regulatory genes [ 14 , 15 ]. These properties of bacteria play a vital role in increasing antimicrobial resistance and pathogenicity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic compound gallic acid (GA) demonstrated the potential to inhibit biofilms of S. mutans [15]. Recently, we also reported that methyl gallate, a GA derivative, can efficiently interfere with the QS regulatory pathways of P. aeruginosa, and inhibit the adhesion, invasion and intracellular survival of S. Typhimurium [16,17]. These properties of bacteria are known to have significant roles in increasing pathogenicity and antimicrobial resistance [18].…”
Section: Introductionmentioning
confidence: 99%